"Seven Days in Lockdown": A Performance Autoethnography of Physical Activity and Mental Health. (June 2022) - Carless, David
COVID-19 increased anxiety levels worldwide. Significant mental health consequences are becoming evident across society, from children to seniors. The pandemic left millions of people out of work or unable to work. It simultaneously increased stress levels for many who remained in work. It made day-to-day life worse—much worse—for a lot of people. I was not immune to these difficulties. Yet, paradoxically, I found that lockdown also offered circumstances to support a degree of recovery or healing. This performance autoethnography draws on diary excerpts I wrote during lockdown in 2020 to explore how various forms of physical activity can help mental health. It offers an alternative perspective on a question that researchers have investigated for decades: When it comes to mental health recovery, what actually works?